Cultivating Students’ Worship Discipline through Mutāba’ah Yawmiyyah: A Qualitative Case Study of School–Family Collaboration in an Indonesian Islamic Junior High School - Fauzia Ramadhani; Budi Santoso Wibowo (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study examines how Mutāba’ah Yawmiyyah cultivates worship discipline among Grade VIII students at SMP IT Dar El-Iman Padang by investigating its implementation, supporting and constraining conditions, and the role of homeroom teachers in school–family collaboration. A qualitative case-study design involved 15 participants comprising the principal, special-program coordinator, homeroom teachers, students, and parents. Data were generated through semi-structured interviews, non-participant observations, and analysis of monitoring books, worship recapitulations, and school documents. Data were analyzed through condensation, coding, thematic categorization, display, and conclusion verification. Credibility was strengthened through source and method triangulation. The program operated through an interconnected cycle of daily recording, parental verification, teacher review, feedback, and follow-up guidance. It supported worship regularity and personal responsibility, but outcomes varied from administrative compliance to behavioral habituation and emerging spiritual awareness. Implementation was strengthened by parental role modeling, school religious routines, teacher guidance, and school–family communication, but constrained by inconsistent monitoring, delayed record completion, uneven parental involvement, difficulty sustaining voluntary worship, and dependence on external reminders. Homeroom teachers acted as guides, evaluators, and intermediaries between school and home. The study distinguishes record completion, behavioral consistency, personal responsibility, and spiritual internalization and proposes a four-stage process: external structuring, socially supported repetition, reflective self-monitoring, and religious internalization. It reconceptualizes Mutāba’ah Yawmiyyah as a collaborative formative mechanism rather than a worship checklist and recommends autonomy-supportive guidance that gradually shifts students from monitored compliance toward meaningful religious self-regulation while protecting privacy and respecting different family capacities and student development.